A catalytically-inactive snake venom Lys49 phospholipase A2 homolog induces expression of cyclooxygenase-2 and production of prostaglandins through selected signaling pathways in macrophages - Moreira, Vanessa (2013)
The effects of a snakevenom Lys-49phospholipaseA2 (PLA2) homolog named MT-II,devoid of enzymatic activity, on the biosynthesis of prostaglandins and protein expression of cyclooxygenase-2(COX-2) and signaling pathways involved were evaluated in mouse macrophages in culture and in peritoneal cells ex vivo. Stimulation of macrophages wit hMT-II leads to production of prostaglandin D2 (PGD2) and prostaglandin E2 (PGE2) and protein expression of COX-2 and microsomal prostaglandin E synthase-1 (mPGES-1). Inhibition of cytosolic PLA2 (cPLA2), but not Ca2+ independent PLA2 (iPLA2) reduced release of PGD2 and PGE2 and expression of COX-2induced by MT-II. Inhibition of nuclear factor kB (NF-kB) significantly reduced MT-II-induced PGE2, but not PGD2 production and COX-2 expression. Inhibitors of either proteinkinase C (PKC), proteintyrosinekinase (PTK),or extracellular signal-regulated kinase(ERK) pathways abrogated MT-II-induced NF-kB activation and reduced COX-2 expression and PGE2 release, whereas the p38 mitogen-activated protein kinase (MAPK) inhibit or reduced MT-II-induced COX-2 expression and PGD2 production.Inhibition of phosphatidylinositol-3-kinase (PI3K) pathway abrogated MT-II-induced NF-kB activation,but affected neither prostaglandins production nor COX-2expression.MT-II-induced production of PGD2 and PGE2 and COX-2 expression were also observed in vivo after intraperitoneal injection into mice. Collectively,our data demonstrate that a catalytically-inactivePLA2 homolog is capable of inducing prostaglandins biosynthesis and COX-2expression in macrophages in both in vitro and in vivo models,indicating that the enzymatic activity of PLA2 is not necessary to trigger these effects. MT-II-activated NF-kB, cPLA2 and distinct protein kinases are the principal steps involved in these cellular events.